2011
DOI: 10.2165/11589250-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoeconomic Considerations in Treating Iron Overload in Patients with β-Thalassaemia, Sickle Cell Disease and Myelodysplastic Syndromes in the US

Abstract: Patients with β-thalassaemia, sickle cell disease (SCD) and myelodysplastic syndromes (MDS) require chronic blood transfusions, which can lead to iron overload and substantial morbidity and mortality. To reduce the excess iron and its deleterious effects, available iron chelation therapy (ICT) in the US includes oral deferasirox or infusional deferoxamine (DFO). The aim of this study was to review and synthesize the available pharmacoeconomic evidence on ICT in patients with β-thalassaemia, SCD and MDS in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…In these circumstances, exogenous apoTf could reverse ineffective erythropoiesis by suppressing TfR1 expression to, in parallel, induce iron-restricted erythropoiesis, derepressing hepcidin, and prevent systemic iron overload. Because upregulation of TfR1 is observed in other diseases of ineffective erythropoiesis with concurrent anemia and iron overload, 73 we propose that TfR1 antagonists would be rational and apparent therapeutic targets, potentially useful to improve erythropoiesis and derepress hepcidin, simultaneously reducing RBC transfusion requirements and preventing/ reversing iron overload. A new treatment approach would greatly benefit this patient population, for whom standard management over the last half-century has consisted of transfusion followed by chelation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In these circumstances, exogenous apoTf could reverse ineffective erythropoiesis by suppressing TfR1 expression to, in parallel, induce iron-restricted erythropoiesis, derepressing hepcidin, and prevent systemic iron overload. Because upregulation of TfR1 is observed in other diseases of ineffective erythropoiesis with concurrent anemia and iron overload, 73 we propose that TfR1 antagonists would be rational and apparent therapeutic targets, potentially useful to improve erythropoiesis and derepress hepcidin, simultaneously reducing RBC transfusion requirements and preventing/ reversing iron overload. A new treatment approach would greatly benefit this patient population, for whom standard management over the last half-century has consisted of transfusion followed by chelation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent blood transfusions are essential for patients with major hemoglobinopathy 33 and bone marrow disorders. 34 Unfortunately, as each unit of transfused blood contains ;250 mg iron and most patients receive 1 blood transfusion of 2 U each month, excess iron rapidly accumulates in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term ramifications of nonadherence to ICTs in persons with iron overload may manifest in severe clinical complications, particularly hepatic failure, iron-induced cardiomyopathy, or pancreatic iron deposition [9]. Based upon cost-effectiveness and cost-utility analyses, DFX has been reported to be cost-effective relative to DFO in the treatment of transfusional iron overload from the perspective of payers both in the U.S. and U.K [12,[17][18][19][20][21][22]. These models, however, assumed high compliance across patient populations, which do not appear to correspond to actual patterns of care [12].…”
Section: Cost Analysismentioning
confidence: 99%
“…Furthermore, even though pharmacoeconomic investigations of DFX have found that the treatment is cost-effective relative to DFO, little attention has focused in the scientific literature upon actual, real-world expenditures associated with both DFO and DFX [12,15,[17][18][19][20][21][22]. Given that patients with SCD that receive chronic blood transfusions require ICTs, good adherence is intuitively warranted to avoid morbidity and mortality associated with iron overload.…”
Section: Introductionmentioning
confidence: 99%